Medical Management of Chronic Cholestatic Liver Diseases - Andrea A Gossard; Keith D Lindor (Canadian Journal of Gastroenterology)
The purpose of the present review is to discuss the diagnosis and management of cholestatic liver diseases. Differential diagnoses to consider are described, including causes of extrahepatic biliary obstruction such as gallstones, strictures, extrabiliary malignancies and pancreatitis. In addition, diseases that cause intrahepatic cholestasis such as primary biliary cirrhosis, primary sclerosing cholangitis, hepatocellular diseases and a variety of miscellaneous causes including drugs that may cause cholestasis are discussed. Primary biliary cirrhosis and primary sclerosing cholangitis are reviewed in detail, and management options are identified. The prognosis of patients with these diseases is discussed, and the Mayo Mathematical Models in Cholestatic Liver Disease for both primary biliary cirrhosis and primary sclerosing cholangitis are provided. Finally, management options for the complications of cholestasis are provided.